Identification of platinum ores via trace element signatures - Hassan, Maisson Mohamed Zeinelabieden (Department of Physics, 2014)
This project studies the natural variation in the elemental composition of processed platinum ore from different extraction locations in South Africa in order to assess whether this provides sufficient information for the elemental fingerprinting" of the material.